Analysis of Arab Coalition Cooperation in Yemen Conflict Settlement - Prasetya, M. Novan; Yahya, Jihan Nadya (Prosiding International Conference on Sustainable Innovation (ICoSI), 2022)
The Yemen crisis is a conflict that has been ongoing for the past dozen years and has not yet subsided. This crisis began with the political instability that existed in the Government of the Republic of Yemen. The formation of the Republic of Yemen in 1990 resulted from the unification of the regions of North Yemen and South Yemen. The two regions agreed to unite because they have similarities in culture, nation, and social conditions. Over time, the Yemeni government has drawn protests from the public because it has not been able to tackle corruption, collusion, nepotism and has also not brought prosperity to its people. This later became a strong reason for the emergence of a separatist movement in Yemen, namely the Houthi Group. The situation was then exacerbated by the Arab Spring phenomenon in 2011 which resulted in an increasing wave of attacks by Houthi. At its peak in 2015 the Houthis then succeeded in taking over the capital Sana’a and besieging the state palace. The president at the time, Mansyur Hadi, then went to Saudi Arabia and asked for help to crush the Houthi rebel group. Saudi Arabia’s involvement in the Yemen Crisis began, Saudi Arabia formed an Arab Coalition consisting of Qatar, Kuwait, the United Arab Emirates (UAE), Bahrain, Egypt, Morocco, Jordan, and Sudan. This Arab coalition then carried out military operations, namely Operation Decisive Storm and Operation Renewal of Hope. Military forces were sent to the border areas of Yemen and Saudi Arabia which are the epicenter of the Houthis’ attacks. It has been seven years since the intervention of the Arab Coalition in the Yemen Crisis, but the situation is getting worse. The crisis that was previously an internal problem in Yemen has now turned into a problem in the Middle East region